Penatalaksanaan Holistik Penyakit Herpes Zoster pada Pasien Remaja Laki-Laki 15 Tahun dengan Pendekatan Kedokteran Keluarga - Nadia Rosmalia Dewi; Dian Isti Angraini (CV. Jasa Sukses Abadi, 2020)
Shingles is clinical manifestations due to reactivation of varicella zoster virus (VZV). in sensory ganglia that were previously exposed to primary varicella infection. The incidence of HZ increases with age and is rarely found in children. Shingles can occur in children who have primary primary infections, immunocompromised conditions, and who are related in the first year of life. The purpose of this study is to Identify internal and external risk factors and clinical problems in patients, as well as holistically managing patients by applying a family doctor based on evidence-based medicine through a patient centered approach and family approach. This study analysis is a case report. Primary data were obtained through history taking (autoanamnesis from the patient and alloanamnesis from the patient's family) physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of study in a qualitative and quantitative manner. Patient A, 15 years old, who has been diagnosed with Herpes Zoster without complications has concerns about his health condition, the patient feels inferior and is afraid that his illness cannot be cured and is afraid of transmitting it to other family members. Patient's expectation is that complaints disappear completely and do not recur, so that they can be comfortable in their normal activities. Limitation of the patient's knowledge of the illness and bad lifestyle is a factor causing problems that occur in patients and families. The diagnosis of shingles in this case is in accordance with several theories and critical studies from recent research. Management has been given in accordance with management guidelines. Good developments were seen in patients ranging from decreased clinical symptoms to behavioral changes after a family-approach and patient-centered Evident Based Medicine intervention.